A Cu-NHC based phosphorescent binuclear iridium(iii)/copper(i) complex with an unpredictable near-linear two-coordination mode. Issue 48 (26th November 2018) - Shi, Chao; Huang, Manli; Li, Qiuxia; Xie, Guohua; Yang, Chuluo; Yuan, Aihua
Abstract : A Cu-NHC based phosphorescent binuclear iridium(iii )/copper(i ) complex with an unpredictable near-linear two-coordination mode has been prepared and shows good optical properties. Abstract : A novel Cu-NHC based phosphorescent binuclear iridium(iii )/copper(i ) complex has been prepared. The copper(i ) center adopts an unpredictable near-linear two-coordination mode with short Cu–N and Cu–C bond lengths and two obvious CH–π interactions, which support its stability in the solid state. It also shows better optical properties (higher luminescence efficiency and shorter emission lifetime) in both solution and solid states relative to the model binuclear copper(i )/copper(i ) complex, and was successfully applied in solution-processed organic light-emitting diodes.